The Inhuman: Reflections on Time - Lyotard, Jean-François 1924-1998; Bennington, Geoffrey; Bowlby, Rachel (California, CA Stanford University Press, 1992)
In this collection of 17 essays, all written or presented between 1980 and 1989, Lyotard addresses a variety of topics related to the transition from modernity to postmodernity.
Originally published in 1988
Keywords: 20th Century (1901-2000); Philosophy; Avant-garde; Postmodernism; Time; France